Syn-eruptive hydrothermal degassing and CO2 fluxes at the Planchón-Peteroa Volcanic complex (Chile-Argentina): evidence from dissolved gases, isotopes, and radon tracers - L. Ruggiero; A. Sciarra; N. Vigide; M.C. Tartarello; H. Barcelona; R. Maffucci; A. Conti; G. Galli; S. Bigi (Journal of Volcanology and Geothermal Research, 2026)

Biosurfactants from marine thermophilic bacilli for mitigating soil dehydration and preventing plant diseases - V. Zammuto; A. Macrì; M. T. Caccamo; S. Magazù; E. Conti; D. Leone; A. Spanò; C. Gugliandolo (International Journal of Environmental Science and Technology, 2026)

Serum concentrations of selenium, selenium species and metals in children newly diagnosed with leukemia: a hospital-based case-control study - Marco Vinceti; Teresa Urbano; Bernhard Michalke; Lauren A. Wise; Maria Caterina Putti; Eloise Pulvirenti; Claudia Favara; Silvia Di Federico; Federico Zagnoli; Giorgia Adani; Annadiletta Donà; Roberta Patti; et al. (Environmental Research, 2026)

Solid biofuel production from torrefaction of urban tree pruning biomass using a combined mixture-process experimental design - Marcos Paulo Patta Granado; Gabriel Luis Alves; Anna Julia Brunheroto Correia; Sonil Nanda; Janusz A. Kozinski; Andrea Cressoni De Conti (Biomass and Bioenergy, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Jellyfish bioactive compounds fueling marine biotechnology in blue economy and biomedicine - Enrico La Spina; Ignazio A. Barbagallo; Cesarina Giallongo; Lucia Longhitano; Paola Leotta; Giuseppe N. Conti; Sebastiano Giallongo; Sofia P. Lombardo; Alberto Felici; Francesco Bellia; Emanuela Tropea; Giovanni Li Volti; et al. (Frontiers in Marine Science, 2026)
Jellyfish, often primarily perceived by the public as a marine nuisance, represent an increasingly valuable and sustainable source of diverse biomolecules with significant potential for the biomedical sciences, in addition to their crucial ecological role within marine ecosystems. This review explores the properties, extraction and applications of key jellyfish-derived compounds, including collagen, peptides, sulfated polysaccharides, glycoproteins and venom components. The relevance of jellyfish as a bioresource is underscored by episodic bloom events in the Mediterranean, where species such as Rhizostoma pulmo (Macri, 1778) have been reported in affected coastal areas. This review provides a critical synthesis of current advances in the extraction, characterization, and biotechnological exploitation of jellyfish-derived bioactive compounds, on ecologically and biotechnologically relevant Mediterranean species, which collectively represent accessible and high-impact targets for marine bioprospecting. Evidence from non-Mediterranean species is also discussed for comparative purposes to contextualize conserved biochemical features across different biogeographical regions. Among jellyfish-derived biomolecules, collagen emerges as the most technologically mature and translationally advanced compound, supported by reproducible extraction protocols, preserved triple-helical structure, cytocompatibility, and compatibility with pre-GMP manufacturing workflows. Recent studies further demonstrate that aquaculture-reared Cassiopea andromeda (Forsskål, 1775) may achieve collagen yields comparable to wild populations (~40–46%) while exhibiting enhanced antioxidant profiles, supporting the feasibility of controlled biofactory approaches. In contrast, peptides, sulfated polysaccharides, and venom components display promising biological activities but remain at earlier stages of technological readiness, requiring further standardization, structure–function elucidation, and regulatory development. Within circular and blue bioeconomy frameworks, jellyfish biomass—particularly from invasive or bloom-forming species such as C. andromeda —offers a concrete opportunity to unlock novel therapeutic solutions and advanced biomaterials, addressing critical unmet medical needs and offering a sustainable alternative to traditional biomedical resources.

Unveiling the effect of curcumin on ion channels of SBMA motoneuron-derived cells and human IPSC-derived neurons: initial electrophysiological findings - Vera Plakhova; Ingrid Battistella; Vladimir A. Martínez-Rojas; Marta Marchioretto; Daniele Arosio; Linda Masello; Luciano Conti; Carlo Musio (European Biophysics Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

Insect-based biopolymers from Orthoptera: An emerging resource for sustainable and active food packaging - Oscar Zannou; Barbara Conti; Linda Abenaim; João K. Lopes; Paula Barciela; Custódio L. Roriz; Miguel A. Prieto; Sandrina A. Heleno; Marcio Carocho; Gulden Goksen (Trends in Food Science & Technology, 2026)

An alternative approach to estimate mismanaged plastic waste at the sub-national scale - Tiago Balieiro Cetrulo; Letícia Stevanato Rodrigues; Camila Sasahara; Sylmara Lopes Francelino Gonçalves Dias; Natália Molina Cetrulo; Francisco Silva Pinto; Costas A. Velis; Melanie Vianna Alencar; Bianca Gabani Gimenez; Carla Isobel Elliff; Luis Américo Conti; Vitória Milanez Scrich; et al. (Marine Pollution Bulletin, 2026)

Associations between per- and polyfluoroalkyl substances and metabolic dysfunction-associated steatotic liver disease in adolescents and young adults: modifying roles of age, lifestyle factors, and PNPLA3 genotype - Shiwen Li; Jiawen Carmen Chen; Elizabeth Costello; Douglas I. Walker; Jesse A. Goodrich; Lily Dara; Lucy Golden-Mason; Ana C. Maretti-Mira; Scott M. Bartell; Veronica M. Vieira; Tanya L. Alderete; Michael I. Goran; et al. (Environmental Research, 2026)

Corrigendum to “Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets” [Applied Soil Ecology 204 (2024) 105710] - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2026)

Mediating role of proteomics in the association between per- and polyfluoroalkyl substance exposure and blood pressure in youth - Jiawen Carmen Chen; Jesse A. Goodrich; Jiawen Liao; Shiwen Li; Qiran Jia; Douglas I. Walker; Elizabeth Costello; Tanya L. Alderete; Michael I. Goran; Damaskini Valvi; Shudi Pan; Brittney O. Baumert; et al. (Environmental Pollution, 2025)

Correction to: Foundations of a learning system for food system transformation under uncertainty - Kai Mausch; Andy Hall; Caroline Hambloch; Costanza Conti; Michael Hauser; Salina Abraham; Philippa Hammond; Enayat A. Moallemi (Food Security, 2025)

Foundations of a learning system for food system transformation under uncertainty - Kai Mausch; Andy Hall; Caroline Hambloch; Costanza Conti; Michael Hauser; Salina Abraham; Philippa Hammond; Enayat A. Moallemi (Food Security, 2025)
Despite a broad consensus on the necessity of fundamental change, endeavors to transform food systems appear to have reached an impasse. Greater engagement with the uncertainty of food systems could open up new ways of triggering transformation directed towards achieving more sustainable and inclusive outcomes. As a way of reorienting current food system change efforts to better embrace uncertainty, we propose a framework for a transformative learning system that serves two aims. First, the framework highlights the importance of locally led action, experimentation, and learning, providing a way of focusing on the core capacities and skills needed to act in the face of uncertainty. Second, it outlines the different types of learning functions that need to operate at different scales of food systems to trigger disruptive, coordinated, and more democratic change processes. The operationalization of this framework necessitates shifts in roles and ways of working across the landscape of food system interventions. The discussion will address the who and how of this potential change, as well as its subsequent impact on the operational modalities of individuals, the process of change itself, and the structures and institutions involved in the process. We argue that embracing uncertainty and the focus on learning has the potential to facilitate a more agile and locally relevant change process. This would allow actors to learn from decentrally pursued food systems reforms, leading to the emergence of diverse pathways that complement on-going efforts and potentially accelerate transformation efforts.

Are environmental factors correlated with the diversity of Phytophthora in organically and conventionally managed citrus orchards in Sicily? Insights from metabarcoding and baiting - Sebastiano Conti Taguali; Federico La Spada; Antonella Pane; Peter J. A. Cock; Beatrix Keillor; David E. L. Cooke; Santa Olga Cacciola (Mycological Progress, 2025)
Phytophthora species pose a significant threat to citrus production in the Mediterranean, particularly in Sicily, a major citrus-producing region. This study explores the diversity and distribution of Phytophthora taxa in Sicilian citrus orchards, addressing the urgent need to tackle increasing agricultural challenges, such as climate change. Specifically, it aimed to evaluate how environmental factors, such as the type of management (organic vs. conventional) and geographical area influence the composition of Phytophthora communities in Sicilian citrus orchards, and whether these communities correlate with tree health. An additional objective was to compare the effectiveness of traditional baiting and high-throughput metabarcoding techniques (targeting the ITS1 region and RPS10 gene) in capturing this diversity, as well as to assess potential shifts in community structure resulting from climate change by comparing current data with historical records. Soil samples were collected from ten citrus-producing areas under two distinct agronomic management and tree health conditions. Traditional baiting recovered 556 isolates of three already described Phytophthora species, while ITS1 metabarcoding identified ten additional taxa, demonstrating higher specificity (99.5% of ITS1 reads classified as Phytophthora compared to 82.5% for RPS10 ). Our findings indicate that geographical location is a key driver of community composition. Although statistical analyses did not reveal significant differences in Phytophthora diversity between organic and conventional management systems, these results provide valuable insights into the factors shaping pathogen communities. These insights are crucial for developing targeted disease management strategies and for understanding how environmental stressors, including climate change, impact pathogen dynamics in Mediterranean citrus orchards. Graphical Abstract

Short-chain per- and polyfluoroalkyl substances associate with elevated alanine aminotransferase: Cross-sectional analysis results from the STRIVE cohort - Bojung Seo; Hongxu Wang; Rachel Maguire; Yukun Liu; Beatrice Smith; Kristin Haller; Marjorie Riggan; David V. Conti; Heinz-Josef Lenz; Kara Wegermann; Antonio Planchart; Giorgio Roccaro; et al. (Environmental Research, 2025)

Evaluating 3D-Printed Pre-separator Inserts in a Fast Screening Impactor for Physicochemical Characterization of Fine Particle Dose Release from Dry Powder Inhalers - Nathan A. Reed; Roee Dar; Nicholas Holtgrewe; Leo N. Y. Cao; Xiaofei Liu; Denise S. Conti; Bryan Newman; Elizabeth Bielski; Jason D. Rodriguez; Changning Guo (AAPS PharmSciTech, 2025)

Isolation of a novel microplastic-degrading bacterial strain: a promising agent for low-density polyethylene remediation - S.B. Cabigliera; D. Gaudioso; D. Chelazzi; L. Conti; B. Muzzi; D. Cantagalli; A. Cincinelli; S. Tegli; A. Jenkins; T. Martellini (Chemosphere, 2025)

Charting the uncharted: Broad-scale benthic habitat distribution in the Brazilian continental margin - Vitor de Souza; Ibon Galparsoro; Tiago B. Gandra; Luis A. Conti; Marinez E. Scherer; Jarbas Bonetti (Estuarine, Coastal and Shelf Science, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Top-down vs bottom-up processes: A systematic review clarifying roles and patterns of interactions in food system transformation - Costanza Conti; Andy Hall; Enayat A. Moallemi; Amar Laila; Christophe Bene; Jessica Fanzo; Matthew Ford Gibson; Line Gordon; Christina Hicks; Kristiaan Kok; Nitya Rao; Ramanan Laxminarayan; et al. (Global Food Security, 2025)

Oxidative gaseous air pollutant exposure interacts with PNPLA3-I148M genotype to influence liver fat fraction and multi-omics profiles in young adults - William B. Patterson; Nathan D. Young; Elizabeth A. Holzhausen; Frederick Lurmann; Donghai Liang; Douglas I. Walker; Dean P. Jones; Jiawen Liao; Zhanghua Chen; David V. Conti; Lida Chatzi; Jesse A. Goodrich; et al. (Environmental Pollution, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

The potential mediating role of the gut microbiome and metabolites in the association between PFAS and kidney function in young adults: A proof-of-concept study - Hailey E. Hampson; Shiwen Li; Douglas I. Walker; Hongxu Wang; Qiran Jia; Sarah Rock; Elizabeth Costello; Petter Bjornstad; Laura Pyle; Jonathan Nelson; Frank D. Gilliland; Zhanghua Chen; et al. (Science of The Total Environment, 2024)

Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2024)

Natural-based solutions to mitigate dietary microplastics side effects in fish - N. Cattaneo; M. Zarantoniello; F. Conti; A. Tavano; A. Frontini; I. Sener; G. Cardinaletti; I. Olivotto (Chemosphere, 2024)

Effect of Mitoquinone on sperm quality of cryopreserved stallion semen - Ahmed R. Elkhawagah; Gian Guido Donato; Mariagrazia Poletto; Nicola A. Martino; Leila Vincenti; Laura Conti; Denis Necchi; Tiziana Nervo (Journal of Equine Veterinary Science, 2024)

Exposure to per- and polyfluoroalkyl substances and alterations in plasma microRNA profiles in children - Yijie Li; Brittney O. Baumert; Nikos Stratakis; Jesse A. Goodrich; Haotian Wu; Shelley H. Liu; Hongxu Wang; Emily Beglarian; Scott M. Bartell; Sandrah Proctor Eckel; Douglas Walker; Damaskini Valvi; et al. (Environmental Research, 2024)

P13-17 Assessment of the efficiency of the literature search of the ten key characteristics of carcinogens in the IARC Monographs evaluation process - C. Facchin; A. De Conti; L. Benbrahim-Tallaa; S. Chittiboyina; S. Ruiz; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2024)

Safflower cake as an ingredient for a composite flour development towards a circular economy: extrusion versus conventional mixing - Carolina A. Antunes Amadeu; Ana Carolina Conti; Carlos Augusto Fernandes Oliveira; Silvia Maria Martelli; Fernanda Maria Vanin (Food Research International, 2024)

CoMMa: A GIS geomorphometry toolbox to map and measure confined landforms - Riccardo Arosio; Joana Gafeira; Laurence H. De Clippele; Andrew J. Wheeler; Veerle A.I. Huvenne; Fabio Sacchetti; Luis A. Conti; Aaron Lim (Geomorphology, 2024)

Environmental pollutant risk factors for worse COVID-19 related clinical outcomes in predominately hispanic and latino populations - Brittney O. Baumert; Hongxu Wang; Shar Samy; Sung Kyun Park; Chun Nok Lam; Kathryn Dunn; Brismar Pinto-Pacheco; Douglas Walker; Julio Landero; David Conti; Leda Chatzi; Howard Hu; et al. (Environmental Research, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Correction to: A1R–A2AR heteromers coupled to Gs and Gi/0 proteins modulate GABA transport into astrocytes - Sofia Cristóvão-Ferreira; Gemma Navarro; Marc Brugarolas; Kamil Pérez-Capote; Sandra H. Vaz; Giorgia Fattorini; Fiorenzo Conti; Carmen Lluis; Joaquim A. Ribeiro; Peter J. McCormick; Vicent Casadó; Rafael Franco; et al. (Purinergic Signalling, 2024)

Biogeography of orchids and their pollination syndromes in small Mediterranean islands - M. Lussu; P. Zannini; R. Testolin; D. Dolci; M. Conti; S. Martellos; A. Chiarucci (Journal of Biogeography, 2024)
Aims Despite the research on orchid in insular conditions, few studies are focused on the spatial distribution of their reproductive syndromes across complex insular systems. By using island species–area relationships (ISAR), we explore orchid biogeography in the Central Western‐Mediterranean islands. In this study, we aim to investigate variation in ISARs using orchid pollination mechanisms as proxies to establish permanent populations explaining how the c and z parameters of ISARs vary among island types and pollination strategies and defining the most influential factors in shaping orchids' distribution. Location Mediterranean Basin. Taxon Orchidaceae. Methods Checklist of native orchids was obtained for 112 islands of Central‐Western Mediterranean Basin. The Arrhenius power function () was used to fit ISARs for the total number of orchids as well as for functional groups defined by the pollination strategies, across different island types. We used GLM to investigate the relation between pollination syndromes with area and isolation as well as elevation, island origin, taxa richness of the source area and habitat diversity. Results We found that ISARs differ between continental and volcanic islands depending on isolation. The z ‐value was found to be higher for more specialized strategies while the c ‐value increases from autogamy to allogamy, supporting the role of these two parameters in understanding distributional dynamics. Distance from the mainland is a negative predictor for all the strategies except when deception is decoupled; island area is a positive predictor only for allogamic, deceptive and food deceptive strategies, while habitat diversity is a positive predictor for allogamic, rewarding and deceptive strategies. Main Conclusions Pollination syndromes contribute in explaining the distribution of orchids in insular conditions. Furthermore, we identified differences in ISARs across pollination syndromes in which the intercept increases when the pollination shifts from a generalist to a more specialized one.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Exposure to perfluoroalkyl substances and longitudinal changes in bone mineral density in adolescents and young adults: A multi-cohort study - Emily Beglarian; Elizabeth Costello; Douglas I. Walker; Hongxu Wang; Tanya L. Alderete; Zhanghua Chen; Damaskini Valvi; Brittney O. Baumert; Sarah Rock; Bruna Rubbo; Max T. Aung; Frank D. Gilliland; et al. (Environmental Research, 2024)

Per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers and dysregulation of MicroRNA expression in humans and animals—A systematic review - Yijie Li; Brittney O. Baumert; Elizabeth Costello; Jiawen Carmen Chen; Sarah Rock; Nikos Stratakis; Jesse A. Goodrich; Yinqi Zhao; Sandrah P. Eckel; Douglas I. Walker; Damaskini Valvi; Michele A. La Merrill; et al. (Environmental Research, 2024)

Breast density in NF1 women: a retrospective study - R. De Santis; G. Cagnoli; B. Rinaldi; D. Consonni; Beatrice Conti; M. Eoli; A. Liguori; M. Cosentino; G. Carrafiello; O. Garrone; M. Giroda; C. Cesaretti; et al. (Familial Cancer, 2024)
Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by neurofibromin haploinsufficiency due to pathogenic variants in the NF1 gene. Tumor predisposition has long been associated with NF1, and an increased breast cancer (BC) incidence and reduced survival have been reported in recent years for women with NF1. As breast density is another known independent risk factor for BC, this study aims to evaluate the variability of breast density in patients with NF1 compared to the general population. Mammograms from 98 NF1 women affected by NF1, and enrolled onto our monocentric BC screening program, were compared with those from 300 healthy subjects to verify differences in breast density. Mammograms were independently reviewed and scored by a radiologist and using a Computer-Aided Detection (CAD) software. The comparison of breast density between NF1 patients and controls was performed through Chi-squared test and with multivariable ordinal logistic models adjusted for age, body mass index (BMI), number of pregnancies, and menopausal status.breast density was influenced by BMI and menopausal status in both NF1 patients and healthy subjects. No difference in breast density was observed between NF1 patients and the healthy female population, even after considering the potential confounding factors.Although NF1 and a highly fibroglandular breast are known risk factors of BC, in this study, NF1 patients were shown to have comparable breast density to healthy subjects. The presence of pathogenic variants in the NF1 gene does not influence the breast density value.

Numerical modeling of the influence of reservoir management on the algal blooms of San Roque - J. Muchiut; M. I. Rodríguez; A. L. Ruibal Conti; M. Ruiz; A. Rodríguez (International Journal of Environmental Science and Technology, 2024)

Associations of per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers with oxidative stress markers: A systematic review and meta-analysis - Jiawen Carmen Chen; Brittney O. Baumert; Yijie Li; Yiping Li; Shudi Pan; Shante Robinson; Bruna Rubbo; Elizabeth Costello; Jie He; Hailey Hampson; Emily Beglarian; Sarah Rock; et al. (Environmental Research, 2023)

Advancing plastic pollution hotspotting at the subnational level: Brazil as a case study in the Global South - Melanie Vianna Alencar; Bianca Gabani Gimenez; Camila Sasahara; Carla Isobel Elliff; Costas A. Velis; Letícia Stevanato Rodrigues; Luis Americo Conti; Sylmara Lopes Francelino Gonçalves-Dias; Tiago Balieiro Cetrulo; Vitória Milanez Scrich; Alexander Turra (Marine Pollution Bulletin, 2023)

P03-14: Cancer Hazard Identification in the IARC Monographs: Recent evaluations for which cancer in experimental animals and toxicological evidence was influential - L. Benbrahim-Tallaa; F. El Ghissassi; A. De Conti; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2023)

OS02-04: Advancing the evaluation of mechanistic evidence in cancer hazard identification: update on the IARC key characteristic (KCs) of carcinogens framework - F. Madia; A. De Conti; F. El Ghissassi; L. Benbrahim-Tallaa; M. Schubauer-Berigan (Toxicology Letters, 2023)

Optimization of FDM 3D printing process parameters to produce haemodialysis curcumin-loaded vascular grafts - Sara Basile; Essyrose Mathew; Ida Genta; Bice Conti; Rossella Dorati; Dimitrios A. Lamprou (Drug Delivery and Translational Research, 2023)
3D printing has provided a new prospective in the manufacturing of personalized medical implants, including fistulas for haemodialysis (HD). In the current study, an optimized fused modelling deposition (FDM) 3D printing method has been validated, for the first time, to obtain cylindrical shaped fistulas. Printing parameters were evaluated for the manufacturing of fistulas using blank and 0.25% curcumin-loaded filaments that were produced by hot melt extrusion (HME). Four different fistula types have been designed and characterized using a variety of physicochemical characterization methods. Each design was printed three times to demonstrate printing process accuracy considering outer and inner diameter, wall thickness, width, and length. A thermoplastic polyurethane (TPU) biocompatible elastomer was chosen, showing good mechanical properties with a high elastic modulus and maximum elongation, as well as stability at high temperatures with less than 0.8% of degradation at the range between 25 and 250 °C. Curcumin release profile has been evaluated in a saline buffer, obtaining a low release (12%) and demonstrating drug could continue release for a longer period, and for as long as grafts should remain in patient body. Possibility to produce drug-loaded grafts using one-step method as well as 3D printing process and TPU filaments containing curcumin printability has been demonstrated. Graphical abstract

Fully convolutional neural networks applied to large-scale marine morphology mapping - Riccardo Arosio; Brandon Hobley; Andrew J. Wheeler; Fabio Sacchetti; Luis A. Conti; Thomas Furey; Aaron Lim (Frontiers in Marine Science, 2023)
In this study we applied for the first time Fully Convolutional Neural Networks (FCNNs) to a marine bathymetric dataset to derive morphological classes over the entire Irish continental shelf. FCNNs are a set of algorithms within Deep Learning that produce pixel-wise classifications in order to create semantically segmented maps. While they have been extensively utilised on imagery for ecological mapping, their application on elevation data is still limited, especially in the marine geomorphology realm. We employed a high-resolution bathymetric dataset to create a set of normalised derivatives commonly utilised in seabed morphology and habitat mapping that include three bathymetric position indexes (BPIs), the vector ruggedness measurement (VRM), the aspect functions and three types of hillshades. The class domains cover ten or twelve semantically distinct surface textures and submarine landforms present on the shelf, with our definitions aiming for simplicity, prevalence and distinctiveness. Sets of 50 or 100 labelled samples for each class were used to train several U-Net architectures with ResNet-50 and VGG-13 encoders. Our results show a maximum model precision of 0.84 and recall of 0.85, with some classes reaching as high as 0.99 in both. A simple majority (modal) voting combining the ten best models produced an excellent map with overall F1 score of 0.96 and class precisions and recalls superior to 0.87. For target classes exhibiting high recall (proportion of positives identified), models also show high precision (proportion of correct identifications) in predictions which confirms that the underlying class boundary has been learnt. Derivative choice plays an important part in the performance of the networks, with hillshades combined with bathymetry providing the best results and aspect functions and VRM leading to an overall deterioration of prediction accuracies. The results show that FCNNs can be successfully applied to the seabed for a morphological exploration of the dataset and as a baseline for more in-depth habitat mapping studies. For example, prediction of semantically distinct classes as “submarine dune” and “bedrock outcrop” can be precise and reliable. Nonetheless, at present state FCNNs are not suitable for tasks that require more refined geomorphological classifications, as for the recognition of detailed morphogenetic processes.

Tumor and peritumoral adipose tissue crosstalk: De-differentiated adipocytes influence spread of colon carcinoma cells - G. Conti; L. Calderan; L.A. Quintero Sierra; A. Conti; R. Ossanna; F. Boschi; P. Marzola; F. Ferrarini; M. Governa; P.M.-J. Lievens; A. Sbarbati (Tissue and Cell, 2023)

Juvenile polyposis diagnosed with an integrated histological, immunohistochemical and molecular approach identifying new SMAD4 pathogenic variants - Andrea Mafficini; Lodewijk A. A. Brosens; Maria L. Piredda; Cristian Conti; Paola Mattiolo; Giulia Turri; Maria G. Mastrosimini; Sara Cingarlini; Stefano F. Crinò; Matteo Fassan; Paola Piccoli; Michele Simbolo; et al. (Familial Cancer, 2022)
Juvenile polyposis (JP) is a rare familial syndrome characterized by the development of numerous hamartomatous polyps of the gastrointestinal tract and by an increased risk of developing gastrointestinal cancers. It follows a pattern of autosomal dominant inheritance and is associated with germline variants of SMAD4 or BMPR1A genes. Differential diagnosis may be difficult based on histology alone, due to morphological similarities to other familial syndromes. Here we report a case of familial JP diagnosed in a 50-years woman with a familial history positive for gastrointestinal cancers and other tumor types. The patient presented with severe iron deficiency anemia and showed numerous polyps in the stomach and jejunum according to endoscopy and imaging. She underwent an intra-gastric laparoscopic removal of the major gastric polyp, followed by jejunal exploration and resection of a segment with multiple neoformations. Histological examination revealed the presence of hamartomatous polyposis. Gastric and intestinal samples were analyzed with next-generation sequencing. Molecular analysis showed that the patient harbored a germline splicing site variant of SMAD4 , c.1139 + 3A > G, which was complemented by different somatic variants of the same gene in the different polyps. Immunohistochemistry for SMAD4 confirmed loss of protein expression in the polyps, with regular expression in normal cells. cDNA sequencing further confirmed the findings. We thus definitively diagnosed the woman as having JP thanks to an integrated approach based on histology, immunohistochemistry and molecular analysis. The identified variants, all previously reported as variants of unknown significance, were classified as pathogenic as they complemented each other leading to SMAD4 loss.

Unraveling the Lagged Effect of Hydro-meteorological Conditions On the Trophic State of a Reservoir By Applying Dynamic Regression - Pablo F. Andreoni; Marcia A. Ruiz; María Inés Rodríguez; Ana Laura Ruibal-Conti (Water Resources Management, 2022)

Correction: International Regulatory Collaboration on the Analysis of Nitrosamines in Metformin-Containing Medicines - David A. Keire; Robert Bream; Uwe Wollein; Schmaler-Ripcke; Annette Burchardt; Massimiliano Conti; Adam Zmysłowski; Peter Keizers; Justin Morin; Jalene Poh; Mark George; Michael Wierer (The AAPS Journal, 2022)

International Regulatory Collaboration on the Analysis of Nitrosamines in Metformin-Containing Medicines - David A. Keire; Robert Bream; Uwe Wollein; Jeannette Schmaler-Ripcke; Annette Burchardt; Massimiliano Conti; Adam Zmysłowski; Peter Keizers; Justin Morin; Jalene Poh; Mark George; Michael Wierer (The AAPS Journal, 2022)
Recalls of some batches of metformin have occurred due to the detection of N -nitrosodimethylamine (NDMA) in amounts above the acceptable intake (AI) of 96 ng per day. Prior to the recalls, an international regulatory laboratory network had been monitoring drugs for nitrosamine impurities with each laboratory independently developing and validating multiple analytical procedures to detect and measure nitrosamines in metformin drugs used in their jurisdictions. Here, we provide an overview of the analysis of metformin active pharmaceutical ingredients (APIs) and drug products with 1090 samples (875 finished dosage forms (FDFs) and 215 API samples) tested beginning in November of 2019 through July of 2020. Samples were obtained internationally by a variety of approaches, including purchased, received from firms via information requests or selected by regional regulatory authorities (either at wholesalers or during GMP inspections). Only one nitrosamine (NDMA) was detected and was only present in some batches of metformin products. For API samples, 213 out of 215 lots tested had no measurable level of NDMA. For FDF samples tested, the number of batches with NDMA above the AI amount for patient safety was 17.8% (156/875). Based on these data, although the presence of NDMA was of concern, 82.2% of the samples of metformin drug products tested met quality and safety standards for patients. Regulatory agencies continue to collaborate extensively and work with marketing authorization holders to understand root causes of nitrosamine formation and agree on corrective actions to mitigate the presence of NDMA in future metformin batches. Graphical abstract

Effects of tetracycline on entomopathogenic nematodes and their bacterial symbionts - M. Clausi; D. Leone; A. Strano; A. Lizio; G. Rappazzo; C. Mulder; E. Conti (Ecotoxicology, 2021)

3D Classification of Cold-Water Coral Reefs: A Comparison of Classification Techniques for 3D Reconstructions of Cold-Water Coral Reefs and Seabed - Larissa Macedo Cruz de Oliveira; Aaron Lim; Luis A. Conti; Andrew J. Wheeler (Frontiers in Marine Science, 2021)
Cold-water coral (CWC) reefs are complex structural habitats that are considered biodiversity “hotspots” in deep-sea environments and are subject to several climate and anthropogenic threats. As three-dimensional structural habitats, there is a need for robust and accessible technologies to enable more accurate reef assessments. Photogrammetry derived from remotely operated vehicle video data is an effective and non-destructive method that creates high-resolution reconstructions of CWC habitats. Here, three classification workflows [Multiscale Geometrical Classification (MGC), Colour and Geometrical Classification (CGC) and Object-Based Image Classification(OBIA)] are presented and applied to photogrammetric reconstructions of CWC habitats in the Porcupine Bank Canyon, NE Atlantic. In total, six point clouds, orthomosaics, and digital elevation models, generated from structure-from-motion photogrammetry, are used to evaluate each classification workflow. Our results show that 3D Multiscale Geometrical Classification outperforms the Colour and Geometrical Classification method. However, each method has advantages for specific applications pertinent to the wider marine scientific community. Results suggest that advancing from commonly employed 2D image analysis techniques to 3D photogrammetric classification methods is advantageous and provides a more realistic representation of CWC habitat composition.

Barcoding helps threatened species: the case of Iris marsica (Iridaceae) from the protected areas of the Abruzzo (Central Italy) - O. De Castro; E. Del Guacchio; E. Di Iorio; A. Di Maio; L. Di Martino; F. Bartolucci; F. Conti (Plant Biosystems, 2020)

Age-related murine hippocampal CA1 laminae oxidative stress measured in vivo by QUEnch-assiSTed (QUEST) MRI: impact of isoflurane anesthesia - Bruce A. Berkowitz; Robert H. Podolsky; Karen Lins Childers; Alexander Gow; Brandy L. Schneider; Scott C. Lloyd; Kelly E. Bosse; Alana C. Conti; Robin Roberts; Ali M. Berri; Emma Graffice; Kenan Sinan; et al. (GeroScience, 2020)
Age-related impairments in spatial learning and memory often precede non-familial neurodegenerative disease. Ex vivo studies suggest that physiologic age-related oxidative stress in hippocampus area CA1 may contribute to prodromal spatial disorientation and to morbidity. Yet, conventional blood or cerebrospinal fluid assays appear insufficient for early detection or management of oxidative stress within CA1 sub-regions in vivo. Here, we address this biomarker problem using a non-invasive MRI index of CA1 laminae oxidative stress based on reduction in R1 (= 1/T1) after anti-oxidant administration. An R1 reduction reflects quenching of continuous and excessive production of endogenous paramagnetic free radicals. Careful motion-correction image acquisition, and avoiding repeated exposure to isoflurane, facilitates detection of hippocampus CA1 laminae oxidative stress with QUEnch-assiSTed (QUEST) MRI. Intriguingly, age- and isoflurane-related oxidative stress is localized to the stratum lacunosum of the CA1 region. Our data raise the possibility of using QUEST MRI and FDA-approved anti-oxidants to remediate spatial disorientation and later neurodegeneration with age in animals and humans.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Developing allometric models to predict the individual aboveground biomass of shrubs worldwide - G. Conti; L. D. Gorné; S. R. Zeballos; M. L. Lipoma; G. Gatica; E. Kowaljow; J. I. Whitworth‐Hulse; A. Cuchietti; M. Poca; S. Pestoni; P. M. Fernandes (Global Ecology and Biogeography, 2019)
Aim Existing global models to predict standing biomass are based on trees characterized by a single principal stem, well developed in height. However, their use in open woodlands and shrublands, characterized by multistemmed species with substantial crown development, generates a high level of uncertainty in biomass estimates. This limitation led us to (a) develop global models of shrub individual aboveground biomass based on simple allometric variables, (b) to compare the fit of these models with existing global biomass models, and (c) to assess whether models fit change when bioclimatic variables are considered. Location Global. Time period Present. Major taxa studied 118 species of shrubs. Methods We compile a database of 3,243 individuals across 49 sites distributed worldwide. Including stem basal diameter, height and crown diameter as predictor variables, we built potential models and compared their fit using generalized least squares. We used mixed effects models to determine if bioclimatic variables improved the accuracy of biomass models. Results Although the most important variable in terms of predictive capacity was stem basal diameter, crown diameter significantly improved the models’ fit, followed by height. Four models were finally chosen, with the best model combining all these variables in the same equation [ R 2 = 0.930, root mean square error (RMSE) = 0.476]. Selected models performed as well as established global biomass models. Including the individual bioform significantly improved the models’ fit. Main conclusions Stem basal diameter, crown diameter and height measures could be combined to provide robust aboveground biomass (AGB) estimates of individual shrub species. Our study supplements well‐established models developed for trees, allowing more accurate biomass estimation of multistemmed woody individuals. We further provide tools for a methodological standardization of individual biomass quantification in these species. We expect these results contribute to improve the quality of biomass estimates across ecosystems, but also to generate methodological consensus on field biomass assessments in shrubs.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Calcium/calmodulin-stimulated adenylyl cyclases 1 and 8 regulate reward-related brain activity and ethanol consumption - Kelly E. Bosse; Farhad Ghoddoussi; Ajay T. Eapen; Jennifer L. Charlton; Laura L. Susick; Kirt Desai; Bruce A. Berkowitz; Shane A. Perrine; Alana C. Conti (Brain Imaging and Behavior, 2019)

Microparticles and autophagy: a new frontier in the understanding of atherosclerosis in rheumatoid arthritis - C. Barbati; M. Vomero; T. Colasanti; F. Ceccarelli; M. Marcosano; F. Miranda; L. Novelli; A. Pecani; Carlo Perricone; F. R. Spinelli; S. Truglia; F. Conti; et al. (Immunologic Research, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Furan-induced transcriptomic and gene-specific DNA methylation changes in the livers of Fischer 344 rats in a 2-year carcinogenicity study - Volodymyr Tryndyak; Aline de Conti; Daniel R. Doerge; Greg R. Olson; Frederick A. Beland; Igor P. Pogribny (Archives of Toxicology, 2017)

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

Altered soil carbon dynamics under different land-use regimes in subtropical seasonally-dry forests of central Argentina - G. Conti; E. Kowaljow; F. Baptist; C. Rumpel; A. Cuchietti; N. Pérez Harguindeguy; S. Díaz (Plant and Soil, 2016)

Fatigue of Metallic Stents: From Clinical Evidence to Computational Analysis - F. Auricchio; A. Constantinescu; M. Conti; G. Scalet (Annals of Biomedical Engineering, 2016)

Optical Characterization of Normal, Benign, and Malignant Thyroid Tissue: A Pilot Study - M. P. Brandao; R. Iwakura; F. S. Basilio; K. Haleplian; A. S. Ito; L. C. Conti de Freitas; L. Bachmann (Journal of Fluorescence, 2015)

Erratum to: Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Comparative safety profiles of intravitreal bevacizumab, ranibizumab and pegaptanib: the analysis of the WHO database of adverse drug reactions - C. Biagi; V. Conti; N. Montanaro; M. Melis; E. Buccellato; M. Donati; A. Covezzoli; R. Amato; L. Pazzi; M. Venegoni; A. Vaccheri; D. Motola (European Journal of Clinical Pharmacology, 2014)

Copper availability assessment of Cu-contaminated vineyard soils using black oat cultivation and chemical extractants - Eduardo Girotto; Carlos A. Ceretta; Gustavo Brunetto; Alcione Miotto; Tadeu L. Tiecher; Lessandro De Conti; Cledimar R. Lourenzi; Felipe Lorensini; Paulo I. Gubiani; Leandro S. da Silva; Fernando T. Nicoloso (Environmental Monitoring and Assessment, 2014)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Copper uptake, accumulation and physiological changes in adult grapevines in response to excess copper in soil - Alcione Miotto; Carlos A. Ceretta; Gustavo Brunetto; Fernando T. Nicoloso; Eduardo Girotto; Júlia G. Farias; Tadeu L. Tiecher; Lessandro De Conti; Gustavo Trentin (Plant and Soil, 2014)

Mapping protein signal pathway interaction in sarcoma bone metastasis: linkage between rank, metalloproteinases turnover and growth factor signaling pathways - Amalia Conti; Virginia Espina; Antonella Chiechi; Giovanna Magagnoli; Chiara Novello; Laura Pazzaglia; Irene Quattrini; Piero Picci; Lance A. Liotta; Maria Serena Benassi (Clinical & Experimental Metastasis, 2014)

A1R–A2AR heteromers coupled to Gs and Gi/0 proteins modulate GABA transport into astrocytes - Sofia Cristóvão-Ferreira; Gemma Navarro; Marc Brugarolas; Kamil Pérez-Capote; Sandra H. Vaz; Giorgia Fattorini; Fiorenzo Conti; Carmen Lluis; Joaquim A. Ribeiro; Peter J. McCormick; Vicent Casadó; Rafael Franco; et al. (Purinergic Signalling, 2013)

Distribution range and ecological niche of Primula marginata Curtis (Primulaceae) - G. Casazza; S. Marsili; L. Granato; E. Conti; V. Noble; A. Selvaggi; L. Minuto (Plant Biosystems, 2013)

Influence of Mitral Valve Anterior Leaflet in vivo Shape on Left Ventricular Ejection - Annalisa Dimasi; Emanuele Cattarinuzzi; Marco Stevanella; Carlo A. Conti; Emiliano Votta; Francesco Maffessanti; Neil B. Ingels; Alberto Redaelli (Cardiovascular Engineering and Technology, 2012)

Aortic Valve Repair via Neo-Chordae Technique: Mechanistic Insight Through Numerical Modelling - Emiliano Votta; Luca Paroni; Carlo A. Conti; Alessandra Pelosi; Andrea Mangini; Paolo D’Alesio; Riccardo Vismara; Carlo Antona; Alberto Redaelli (Annals of Biomedical Engineering, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Mapping of main and epistatic effect QTLs associated to grain protein and gluten strength using a RIL population of durum wheat - Veronica Conti; Pablo F. Roncallo; Valeria Beaufort; Gerardo L. Cervigni; Ruben Miranda; Carlos A. Jensen; Viviana C. Echenique (Journal of Applied Genetics, 2011)

Mitral Valve Patient-Specific Finite Element Modeling from Cardiac MRI: Application to an Annuloplasty Procedure - Marco Stevanella; Francesco Maffessanti; Carlo A. Conti; Emiliano Votta; Alice Arnoldi; Massimo Lombardi; Oberdan Parodi; Enrico G. Caiani; Alberto Redaelli (Cardiovascular Engineering and Technology, 2011)

Variation in folate pathway genes and distal colorectal adenoma risk: a sigmoidoscopy-based case–control study - A. Joan Levine; Won Lee; Jane C. Figueiredo; David V. Conti; David J. Vandenberg; Brian D. Davis; Christopher K. Edlund; Susanne M. Henning; David Heber; Mariana C. Stern; Robert W. Haile (Cancer Causes & Control, 2011)

Genes involved with folate uptake and distribution and their association with colorectal cancer risk - Jane C. Figueiredo; A. Joan Levine; Won H. Lee; David V. Conti; Jenny N. Poynter; Peter T. Campbell; David Duggan; Juan Pablo Lewinger; Maria Elena Martinez; Cornelia M. Ulrich; Polly Newcomb; John Potter; et al. (Cancer Causes & Control, 2010)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Olive oil adulterated with hazelnut oils: simulation to identify possible risks to allergic consumers - M. Arlorio; J.D. Coisson; M. Bordiga; F. Travaglia; C. Garino; L. Zuidmeer; R. Van Ree; M.G. Giuffrida; A. Conti; A. Martelli (Food Additives & Contaminants: Part A, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

γ-irradiation of PEGd,lPLA and PEG-PLGA Multiblock Copolymers: II. Effect of Oxygen and EPR Investigation - R. Dorati; C. Colonna; C. Tomasi; I. Genta; T. Modena; A. Faucitano; A. Buttafava; B. Conti (AAPS PharmSciTech, 2008)

Nitrous oxide emissions from soil during soybean [(Glycine max (L.) Merrill] crop phenological stages and stubbles decomposition period - Ignacio A. Ciampitti; Esteban A. Ciarlo; Marta E. Conti (Biology and Fertility of Soils, 2008)

Are large‐scale distributional shifts of the blue‐winged macaw ( Primolius maracana ) related to climate change? - Maria Flávia Conti Nunes; Mauro Galetti; Stuart Marsden; Ricardo Scachetti Pereira; A. Townsend Peterson (Journal of Biogeography, 2007)
Aim To evaluate whether observed geographical shifts in the distribution of the blue‐winged macaw ( Primolius maracana ) are related to ongoing processes of global climate change. This species is vulnerable to extinction and has shown striking range retractions in recent decades, withdrawing broadly from southern portions of its historical distribution. Its range reduction has generally been attributed to the effects of habitat loss; however, as this species has also disappeared from large forested areas, consideration of other factors that may act in concert is merited. Location Historical distribution of the blue‐winged macaw in Brazil, eastern Paraguay and northern Argentina. Methods We used a correlative approach to test a hypothesis of causation of observed shifts by reduction of habitable areas mediated by climate change. We developed models of the ecological niche requirements of the blue‐winged macaw, based on point‐occurrence data and climate scenarios for pre‐1950 and post‐1950 periods, and tested model predictivity for anticipating geographical distributions within time periods. Then we projected each model to the other time period and compared distributions predicted under both climate scenarios to assess shifts of habitable areas across decades and to evaluate an explanation for observed range retractions. Results Differences between predicted distributions of the blue‐winged macaw over the twentieth century were, in general, minor and no change in suitability of landscapes was predicted across large areas of the species’ original range in different time periods. No tendency towards range retraction in the south was predicted, rather conditions in the southern part of the species’ range tended to show improvement for the species. Main conclusions Our test permitted elimination of climate change as a likely explanation for the observed shifts in the distribution of the blue‐winged macaw, and points rather to other causal explanations (e.g. changing regional land use, emerging diseases).

Chronic administration of olanzapine induces metabolic and food intake alterations: a mouse model of the atypical antipsychotic-associated adverse effects - R. Coccurello; A. Caprioli; O. Ghirardi; R. Conti; B. Ciani; S. Daniele; A. Bartolomucci; A. Moles (Psychopharmacology, 2006)

Thrusting and faulting in metamorphic and sedimentary units of Ligurian Alps: an example of integrated field work and geochemical analyses - F. Piana; S. Tallone; S. Cavagna; A. Conti (International Journal of Earth Sciences, 2006)

Diet and cooling interactions on physiological responses of grazing dairy cows, milk production and composition - M. R. Gallardo; S. E. Valtorta; P. E. Leva; M. C. Gaggiotti; G. A. Conti; R. F. Gregoret (International Journal of Biometeorology, 2005)

Expression of the ?-carotene desaturase gene in sunflower - M Fambrini; M Salvini; A Conti; V Michelotti; C Pugliesi (Plant Biosystems, 2004)

A phylogenetic analysis of Apostasioideae (Orchidaceae) based on ITS, trnL-F and matK sequences - A. Kocyan; Y.-L. Qiu; P. K. Endress; E. Conti (Plant Systematics and Evolution, 2004)

Oxygen supply modulates MCP-1 release in monocytes from young and aged rats: Decrease of MCP-1 transcription and translation is age-related - M. Reale; C. Di Giulio; M. Cacchio; R.C. Barbacane; A. Grilli; G. Bianchi; M. Di Gioacchino; M. Felaco; P. Conti (Molecular and Cellular Biochemistry, 2003)

The importance of microscopic examination in the management of desquamative diseases of the scalp - Ismael A. Conti Diaz; Eduardo Civila; Rafael Veiga (Mycopathologia, 2002)

Inhibition of MCP-1 and MIP-2 transcription and translation by mimosine in muscle tissue infected with the parasite Trichinella spiralis - Pio Conti; Stavros Frydas; Marcella Reale; Renato C. Barbacane; M. Di Gioacchino; M. Felaco; A. Trakatellis (Molecular and Cellular Biochemistry, 2002)

Geochemical changes at the Bagni di Triponzo thermal spring during the Umbria-Marche 1997–1998 seismic sequence - F. Quattrocchi; R. Pik; L. Pizzino; M. Guerra; P. Scarlato; M. Angelone; M. Barbieri; A. Conti; B. Marty; E. Sacchi; G.M. Zuppi; S. Lombardi (Journal of Seismology, 2000)

Influence of feeding precursors on tropane alkaloid production during an abiotic stress in Datura innoxia transformed roots - M. Boitel-Conti; J-C. Laberche; A. Lanoue; C. Ducrocq; B.S. Sangwan-Norreel (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Impact of extremely low frequency electromagnetic fields on CD4 expression in peripheral blood mononuclear cells - Mario Felaco; Marcella Reale; Alfredo Grilli; Maria A. De Lutiis; Renato C. Barbacane; Silvano Di Luzio; Pio Conti (Molecular and Cellular Biochemistry, 1999)

Vitamin B6-deficient diet plus 4-deoxypyridoxine (4-DPD) reduces the inflammatory response induced by T. spiralis in diaphragm, masseter and heart muscle tissue of mice - S. Frydas; N. Papaioanou; I. Vlemmas; I. Theodoridis; G. Anogiannakis; D. Vacalis; A. Trakatellis; R.C. Barbacane; M. Reale; P. Conti (Molecular and Cellular Biochemistry, 1999)

IgG, IgG1 and IgM response in Trichinella spiralis-infected mice treated with 4-deoxypirydoxine or fed a Vitamin B6-deficient diet - S. Frydas; M. Reale; D. Vacalis; R.C. Barbacane; F.C. Placido; I. Cataldo; M. Di Gioacchino; E. Karagouni; E. Dotsika; G. Anogiannakis; A. Trakatellis; P. Conti (Molecular and Cellular Biochemistry, 1999)

Calcium dependent shifts of Na + channel activation correlated with the state dependence of calcium-binding to the pore - A. Boccaccio; O. Moran; F. Conti (European Biophysics Journal, 1998)

Induction of monocyte chemotactic protein-1 (MCP-1) and TNF alpha by Trichinella spiralis in serum of mice in vivo - M. Reale; S. Frydas; R.C. Barbacane; F.C. Placido; I. Cataldo; P. Conti; D. Vacalis; A. Trakatellis; G. Anogianakis; M. Felaco; M. Di Giocchino (Molecular and Cellular Biochemistry, 1998)

Infra-red laser irradiation enhances interleukin-1 receptor antagonist, increases 3H-thymidine incorporation and the release of [3H]arachidonic acid in human monocytes - Marcella Reale; Claudio Orso; Maria Luisa Castellani; Renato Carmine Barbacane; Fernanda Cristina Placido; Ettore Porreca; Concetta Di Febbo; Ivana Cataldo; Demetrio Vacalis; G. Anogianakis; A. Trakatellis; Pio Conti (Molecular and Cellular Biochemistry, 1997)

Protective effects of melatonin in mice infected with encephalitis viruses - D. Ben-Nathan; G. J. M. Maestroni; S. Lustig; A. Conti (Archives of Virology, 1995)

Different patterns of replication in influenza virus-infected KB cells - G. Conti; P. Valcavi; A. Natali; G. C. Schito (Archives of Virology, 1980)